The Influence of Organizational Culture and Corporate Commitment on Occupational Health and Safety (OHS) Culture and it’s Impact on Employee Performance at PT Kalimantan Jawa Gas - Pranandio, Muhammad Azka; Levyda, Levyda; Kholil, Kholil (Dinasti International Journal of Education Management and Social Science, 2025)
Occupational health and safety (OHS) is essential for ensuring safe and sustainable operations, especially in high-risk industries such as the gas sector. PT Kalimantan Jawa Gas (KJG), a company engaged in natural gas transmission between Kalimantan and Java, faces operational challenges including potential gas leaks, explosions, and exposure to hazardous substances. Despite initiatives such as management visits, safety culture campaigns, and OHS audits, field data indicate ongoing issues with employee compliance in using personal protective equipment and reporting near-miss incidents. This study examines the influence of organizational culture and corporate commitment on OHS culture and its effect on employee performance at PT Kalimantan Jawa Gas. Data were collected using structured questionnaires administered to 51 permanent employees through saturated sampling and analyzed using Partial Least Squares (PLS) via SmartPLS software. The results show that organizational culture significantly affects employee performance but not OHS culture, while corporate commitment significantly influences OHS culture but not employee performance. OHS culture, in turn, has a significant positive impact on employee performance. The study concludes that enhancing employee performance requires strengthening organizational culture and fostering a strong OHS culture through committed workplace safety practices, continuous training, leadership role modeling, and consistent monitoring.